2006
DOI: 10.1109/tnano.2006.880908
|View full text |Cite
|
Sign up to set email alerts
|

Noise in Silicon Nanowires

Abstract: Abstract-The current-voltage and noise characteristics of bridging silicon wires have been measured at room temperature. From the linear current-voltage characteristics the bulk and contact resistance contributions are extracted and modeled. The excess noise observed at low frequencies is interpreted in terms of bulk and contact noise contributions, with the former comparable, in terms of Hooge parameter values, to the low noise levels observed in high-quality silicon devices. The contact noise is significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 10 publications
2
59
0
Order By: Relevance
“…Due to the high surfaceto-volume ratio of nanowires, it is expected that noise may be larger in such devices compared with similar structures based on bulk substrates. However, low Hooge's constants (≈1 × 10 −5 ) have been calculated for SiNW resistors where the noise of the reported devices with the lowest resistivity was analyzed by using a simple model in terms of the bulk and contact resistances [39]. While the Hooge's constant determined for the SiNW FETs reported here is not as dramatically small as this previous report, as shown in Fig.…”
Section: Noise Measurementsmentioning
confidence: 52%
See 1 more Smart Citation
“…Due to the high surfaceto-volume ratio of nanowires, it is expected that noise may be larger in such devices compared with similar structures based on bulk substrates. However, low Hooge's constants (≈1 × 10 −5 ) have been calculated for SiNW resistors where the noise of the reported devices with the lowest resistivity was analyzed by using a simple model in terms of the bulk and contact resistances [39]. While the Hooge's constant determined for the SiNW FETs reported here is not as dramatically small as this previous report, as shown in Fig.…”
Section: Noise Measurementsmentioning
confidence: 52%
“…In addition, semiconductor nanowire devices have no body contact; therefore, charge-pumping techniques [24], [34], [37] cannot be used to investigate charge trapping centers. However, the trapping and detrapping of charge carriers from the nanowire conduction channel lead to low-frequency noise [16], [38], [39]. Under some conditions (such as at low temperatures or in extremely small nanowire devices), the trapping and emission of carriers by discrete interface or border traps lead to experimentally observed RTSs.…”
Section: Noise Measurementsmentioning
confidence: 99%
“…Similarly, the noise level of conventional NW devices fabricated by evaporating metal for contacts was also found to be very high. The noise level in our self-welded Si NWs was found to be at least two orders of magnitude better than that of CNTs and NW devices [309]. The superior characteristics were the result of the highly epitaxial bonding or welding between two NWs and NW-electrodes.…”
Section: B Contact Resistance and Noise In Pdsmentioning
confidence: 74%
“…Also, noise measurement can be used as a figure of merit; the applicability of a certain technology can be limited by the noise the devices produce (see Fig. 19) [309]. This observation also shows the importance of a good understanding of noise characteristics of semiconductor NWs.…”
Section: B Contact Resistance and Noise In Pdsmentioning
confidence: 99%
“…Additionally, degradation in the performance of SiNW-based devices due to metal catalysts and non-uniform dopant distribution [19][20][21][22] does not exist in EFN biosensors because EFNs are electrostatically shaped inside singlecrystalline silicon. The EFN configuration allows the channel to be sufficiently removed from the Si/SiO 2 interface, 23 which is the dominant noise source in SiNWs [24][25][26][27][28][29] as well as in inversion-type planar devices 30 (and in the double-gate nanowire, where the conduction is due to the formation of an inversion layer at the silicon/SiO 2 interface). It was recently demonstrated that the low-frequency noise originating from charge trapping/detrapping at the Si/SiO 2 interface is the prevailing noise source in wet environments, as the noise-level dependency on ion concentration and pH level is negligible.…”
Section: Introductionmentioning
confidence: 99%